COVID-19 cases, deaths, vaccinations and Malaysian Islamic stock market returns / Lain-Tze Tee and Si-Roei Kew - Tee, Lain-Tze; Kew, Si-Roei (Faculty of Business and Management, 2022)
Coronavirus (COVID-19) has been the greatest disrupting pandemic that results in economy and social devastations. This study aims to explore the impact of novel COVID-19 pandemic on Islamic stock market returns in Malaysia. We find that COVID-19 new cases exert negative and significant effect on Islamic stock market returns. In addition, COVID-19 deaths significantly and adversely influence Islamic stock market returns. Particularly, the findings reveal that higher levels of COVID-19 new cases and deaths tend to reduce Islamic stock returns in Malaysia. Interestingly, we document that vaccinations have no impact in influencing Islamic stock market returns, signifying that vaccinations are not effective in improving Islamic stock market returns in Malaysia over the sample period. Our findings provide important implications for academics, policymakers and investors to comprehend the effect of COVID-19 on Islamic stock returns. The results suggest that Islamic stock investments in Malaysia do not show as a superior investment option during the health crisis.